(untitled) (Conferencea, 2022)
The article explores the integral and differential features of English logistic terms, which manifest themselves in translation that brought into the terminological system based on cognition that has become essential at this time. The importance of producing a bilingual English and Uzbek dictionary of logistics terminology is stressed in given materials.